Enhanced E. huxleyi carbonate counterpump as a positive feedback to increase deglacial pCO2sw in the Eastern Equatorial Pacific. (15th May 2021) - Balestrieri, Chiara; Ziveri, Patrizia; Grelaud, Michaël; Mortyn, P. Graham; Agnini, Claudia
Abstract: The modern Eastern Equatorial Pacific (EEP) Ocean is a high nutrient low chlorophyll (HNLC) upwelling region and a large oceanic source of carbon to the atmosphere. During the last deglaciation, the EEP played a major role in the outgassing of carbon dioxide into the atmosphere from the upwelling surface water system of CO2 -enriched deep-water masses originating from the Southern Ocean. The EEP upwelling system is also fertilizing the surface waters and enhancing the biological pump. Here we present data on the mass and calcification dynamics of the coccolithophore species Emiliania huxleyi spanning the last 30 ky at Site ODP 1238 (1°52.310′S, 82°46.934′W; 2203 m) in the EEP. Our results show an increased coccolith calcification degree during times of high p CO2 and low surface water pH conditions; this unexpected result is tentatively explained as related to changes in homeostasis equilibrium at the site of calcification and between the cell and the seawater environment. We estimated the E. huxleyi particulate inorganic to organic carbon ratio (PIC:POC) in order to detect changes in the carbonate counter-pump to carbon pump activity, which can act as either a positive or negative feedback to atmospheric CO2 modulating air-sea gas exchange. Our study indicates an enhanced coccolithophore biological pump during the last glacial that could have buffered, at least partially, the excess of p CO2atm via absorption into the ocean. Finally, during the last deglaciation, the enhanced carbonate counter pump was a major source of high p CO2sw in the EEP surface ocean. Highlights: Increased coccolith calcification degree at high p CO2 and low surface water pH. Enhanced glacial E. huxleyi biological pump as a buffer to the excess of p CO2atm . Enhanced deglacial E. huxleyi counterpump as a major source of high p CO2sw .